(untitled) (Bangladesh Journal of Medical Science, 2025)
Objective To evaluate the effects of exercise interventions on HbA1C, fasting blood glucose (FBG), lipid profiles, blood pressure, anthropometric components, insulin, Homeostasis Model Assessment for Insulin Resistance (HOMA-IR), and inflammatory markers among type 2 diabetes patients. Methods We conducted a meta-analysis of randomized control trials (RCTs). Seven electronic databases, namely CINAHL, the Cochrane Library, Embase, Ovid-Medline, PubMed, Scopus, and Web of Science were searched from inception to September 12, 2022 to identify RCTs assessing the effects of exercise for type 2 diabetes. Hedges’ g and 95% confidence interval (CI) were calculated as the pooled estimates using a random-effects model, and a two-sided P of <0.05 was considered statistically significant. Moderator analyses were used to test the effect of potential moderators on trial effectiveness. Results In total, 126 RCTs involving 7155 people with type 2 diabetes were included. Exercise interventions significantly reduced the primary outcomes, HbA1C and FBG, with a Hedges’ g of -0.67 and -0.76 respectively. Significant effects on the secondary outcomes that included lipid profiles, blood pressure, anthropometric components, insulin, HOMA-IR, and inflammatory markers with Hedges’ g values ranging from -0.26 to -0.78. Moderator analyses revealed that the effect size for FBG significantly different among the four intervention types, and there was a significant association between FBG’s effect size and the percentage of men. Conclusions The results from this meta-analysis demonstrated the importance of exercise interventions on type 2 diabetes-related outcomes. BJMS, Vol. 24 No. 04 October’25 Page : 1260-1303